Dinamika Agresivitas Pajak: Pengaruh Leverage, Likuiditas, Intensitas Modal, dan Peran Moderasi Corporate Governance Perception Index (CGPI) - Septianingrum Nisa; Pancawati Hardiningsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to prove (1) the effect of leverage on tax aggressiveness, (2) the effect of liquidity on tax aggressiveness, (3) the effect of capital intensity on tax aggressiveness, (4) corporate governance perception index (CGPI) can moderate the effect of leverage on tax aggressiveness, (5) corporate governance perception (CGPI) can moderate the effect of liquidity tax aggressiveness, (6) corporate governance perception index (CGPI) can moderate the effect of capital intensity on tax aggressiveness. To achieve the research used was quantitive using secondary data obtained from the company’s annual financial reports. The population of this research is all companies registered in the Corporate Governance Perception Index (CGPI) for the 2018-2021 periode, totalis 48 companies. The sampling technique in this research used puosive sampling with a total sample of 31 companies. The data analysis technique used is panel data regression model analysis. The research results show that (1) Leverage has no significant effect on tax aggressiveness, (2) Liquidity has a significant positive effect on tax aggressiveness, (3) Capital intensity has a significant positive effect on tax aggressiveness, (4) Corporate governance perception index (CGPI) cannot moderates the effect of leverage on tax aggressiveness, (5) Corporate governance perception index (CGPI) can moderate the effect of liquidity on tax aggressiveness, (6) Corporate governance perception index (CGPI) can moderate the effect of capital intensity on tax aggressiveness.